ANALISIS KADAR TOTAL FENOL DAN FLAVONOID PADA PRODUK TEH OOLONG YANG BEREDAR DI PASARAN: Analysis Total Phenol And Total Flavonoid Contents In Some Oolong Tea Products On The Market - Ardi Rustamsyah; Farid Perdana; Anna zakiah; Anita Khairunnisa (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
Oolong tea is a type of tea that is processed using semi-fermentation. Oolong tea has a group of bioactive components, namely polyphenols, one of the phenolic compounds is flavonoids, which are the largest group of polyphenols which are also very effective as antioxidants. This study aims to determine the levels of total phenols and total flavonoids in 5 (five) oolong tea products alre ady on the market. Analysis of total phenol content used the Folin-Ciocalteu method with gallic acid as a comparison, while analysis of total flavonoid content used a complex colorimetric method with quercetin as a comparison and wavelength absorption measurements using a spectrophotometer. The results of the research showed that the highest total phenol content was found in sample D of oolong tea on the market, namely 8.2849 ± 0.7137 mgGAE/g sample, and the highest total flavonoid content was in sample E oolong tea, namely 0.2932 ± 0.0031 mgQE/g sample.